Left Atrial Enhancement Correlates With Myocardial Conduction Velocity in Patients With Persistent Atrial Fibrillation - Ali, Rheeda L.; Qureshi, Norman A.; Liverani, Silvia; Roney, Caroline H.; Kim, Steven; Lim, P. Boon; Tweedy, Jennifer H.; Cantwell, Chris D.; Peters, Nicholas S. (Frontiers in Physiology, 2020)
Background: Conduction velocity (CV) heterogeneity and myocardial fibrosis both promote re-entry, but the relationship between fibrosis as determined by left atrial (LA) late-gadolinium enhanced cardiac magnetic resonance imaging (LGE-CMRI) and CV remains uncertain. Objective: Although average CV has been shown to correlate with regional LGE-CMRI in patients with persistent AF, we test the hypothesis that a localized relationship exists to underpin LGE-CMRI as a minimally invasive tool to map myocardial conduction properties for risk stratification and treatment guidance. Method: 3D LA electroanatomic maps during LA pacing were acquired from eight patients with persistent AF following electrical cardioversion. Local CVs were computed using triads of concurrently acquired electrograms and were co-registered to allow correlation with LA wall intensities obtained from LGE-CMRI, quantified using normalized intensity (NI) and image intensity ratio (IIR). Association was evaluated using multilevel linear regression. Results: An association between CV and LGE-CMRI intensity was observed at scales comparable to the size of a mapping electrode:-0.11m/s per unit increase in NI (P<0.001) and -0.96m/s per unit increase in IIR (P<0.001). The magnitude of this change decreased with larger measurement area. Reproducibility of the association was observed with NI, but not with IIR. Conclusion: At clinically relevant spatial scales, comparable to the area of a mapping catheter electrode, LGE-CMRI correlates with CV. The measurement scale is important in accurately quantifying the association of CV and LGE-CMRI intensity. Importantly, NI, but not IIR, account for changes in the dynamic range of CMRI and enables the quantitative reproducibility of the association.